Registered nurses' experience as disaster preparedness coordinators during a major incident: A qualitative study. Issue 1 (21st September 2021) - Murphy, Jason P.; Hörberg, Anna; Rådestad, Monica; Kurland, Lisa; Rüter, Anders; Jirwe, Maria
Abstract: Aims: To explore registered nurses' experiences as disaster preparedness coordinators of hospital incident command groups' during a major incident. Design: A qualitative descriptive design using semi‐structured interview. Methods: This was a qualitative study based on one focus group discussion and six individual follow‐up interviews. Participants were registered nurses in their capacity as disaster preparedness coordinators with experience from Major Incident simulations and a real‐life Major Incident. The interviews were transcribed verbatim and analysed using content analysis. The COREQ checklist was used for reporting the findings. Results: The analysis of data generated the main category: Expectations, previous experience and uncertainty affect hospital incident command group response during a Major Incident and three categories, (I) Gaining situational awareness (containing two subcategories), (II) Transitioning to management (containing three subcategories) and (III) Actions taken during uncertainty (containing two subcategories).